Joining of non-ferrous metals - Samuelsson, Oscar; Tillberg, Isak (My University, 2023)
The subframe is a large component in a car and is important for meeting the cost, weight and sustainability targets. A light and cost-effective aluminium subframe is therefore interesting for future use. The joining of high-pressure die casted components and extruded aluminium beams was investigated in order to develop a geometrically complex and lightweight subframe. A literature study on possible joining methods and alternative casting processes were carried out and then possible design of joints were illustrated in the report. Mechanical testing of welded joints between components of different die-casting processes and extruded aluminium was conducted. Adhesive bonding, flow-drill screwdriving, hybrid joint of adhesive and flow-drill screwdriving as well as MIG-, TIG- and laser welding were recommended for continued research
Keywords: Aluminium; Aluminum; Wrought; Die-casted; Extruded; High Pressure; Casting; Joining; Non-ferrous; Welding; Adhesive; Riveting; Flow-Drill; Rheocasting; Semi-Solid; Automotive; Subframe